(untitled) (Castilla. Estudios de Literatura, 2017)
In this essay I study the link between the epistolary relationship between Ernestina de Champourcin and Carmen Conde and their simultaneous poetic production. In the light of the concept of a room of one’s own as a essential and necessary space for creative writing elaborated by Virginia Woolf’s eponymous book, I argue that, the epistolary discourse functions as a room of one’s own where both poets try to attain an aesthetic authenticity that was limited by patriarchal society at the beginning of the 20th century in Spain. The presence of the interlocutor, the doubling of the poetic voice, and the metapoetic poems converge in our responsibility as critics to place the poets epistolary at the forefront, since this is used as a workshop and a free space for the development of the poets’ aesthetics.